So You are Getting Married in Florida! - Donna Peacock; Heidi L. Radunovich (EDIS)
Revised! FCS2179, a 5-page fact sheet by Donna Peacock and Heidi Radunovich, explains everything you need to know about how to apply for a Florida marriage license and its costs and requirements. Includes information on how marriage preparation classes can reduce the license fee and on how to go about the name-change process after marriage. Revised to update and clarify information about Florida marriage regulations and procedures. Published by the UF Department of Family, Youth and Community Sciences, November 2006.